Dynamic manoeuvres of KCS with CFD free-running computation and system-based modelling. (1st December 2021) - Jin, Yuting; Yiew, Lucas J.; Zheng, Yingying; Magee, Allan R.; Duffy, Jonathan; Chai, Shuhong
Abstract: Future state projection is an important prerequisite for the maritime autonomous surface ships (MASS) to initiate a collision-avoidance manoeuvre. Forecasts of MASS′ trajectories and motions are fundamentally based on the vessel's mathematical manoeuvring model, which is also referred to as the hydrodynamic digital twin nowadays. Using the benchmark container ship KCS as an object of study, this paper adopts a 3-DOF modular-type manoeuvring (MMG) model to predict the vessel trajectories in calm water and under the presence of steady current and regular waves. The current effects are treated as additional ship over water speed, while the wave effects are considered by superimposing the mean second-order wave drift loads to the calm water hull hydrodynamics. Concurrently, selected manoeuvring cases including turning circle and zig-zag are solved using the unsteady Reynolds-averaged Navier-Stokes (uRANS) equations based CFD method, where a hierarchy of overset grids is utilised to allow self-propulsion and active rudder steering. The computed vessel trajectories and velocities are compared with that predicted by the MMG model and show reasonable agreement. The wave loads experienced by the vessel when turning in waves are also analysed and discussed. Highlights: System-based simulation of KCS manoeuvrability with 3-DoF MMG model. uRANS computations of KCS dynamic manoeuvres in calm water, and under environmental disturbances. Validation against published benchmark model test results for calm water conditions. Comparison is made between MMG and uRANS simulations.